IMPACT OF SURVIVAL STRATEGIES ON ORGANIZATIONAL INNOVATIVENESS IN CONSTRUCTION COMPANIES IN NIGERIA - Clement, M. Clement; Dr. C. Amah; Prof. C.O. Ofurum (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2022)
This study investigated the relationship between survival strategies and organizational innovativeness in construction companies in Nigeria. The study had differentiation and focus strategy as dimensions of survival strategies. The cross-sectional form of the quasi-experimental research design was adopted for this work. A population of 1851 (one thousand eight hundred and fifty-one) was obtained. The Krejcie and Morgan sample size determination table was used to arrive at a sample size of 331 (three hundred and thirty-one). The questionnaire was the main instrument for data collection. Construct and convergent validity were carried out and reliability was tested using the Cronbach Alpha test. Hypotheses were tested using Pearson Moment Correlation. Findings revealed a significant relationship between the dimensions of survival strategies and organizational innovativeness. The findings further reveal a strong and positive relationship between differentiation, focus strategy, and innovativeness of construction companies thus we conclude that survival strategies significantly and proportionately predict the organizational innovativeness level of construction companies. Therefore, we recommended that construction firms should adopt survival strategies (differentiation and focus strategy) in order for them to be more innovative. Managers should encourage employees to think beyond the present situation.